A Methodological Appraisal of the Application of the Hare Psychopathy Checklists in Forensic Setting - Ruwan, Ibrahim Ignatius Felix; Zamani, Andrew (NIU Journal of Social Sciences; Vol 7 No 3 (2021): KIU Journal of Social Sciences, Vol. 7 No. 3, September 2021, 2021)
Psychopathy is seen as a personality disorder defined by a cluster of interpersonal affective lifestyle and antisocial traits and behavior including grandiosity, egocentricity, deceptiveness, shallow emotion, lack of empathy or remorse, irresponsibility and impulsivity and tendency to violate social norms. The paper examined the use of the PCL-R in other climes. Investigation revealed that 90% of cases in the United States were decided using the PCL-R both at the state and federal courts. The PCL-R is also used in expert witnessing and testimony and also used to deal with charges of kidnapping, attempted murder, sexual assault, rape, robbery, long term offenders and dangerous offenders. Investigation also revealed that the PCL-R is used in sentence cases, parole hearing and death penalty sentencing in Canada. The paper therefore recommends that the Hare psychopathic checklist (PCL-R) should be validated and adapted in Nigeria and be used in the criminal justice system as a research instrument for research purposes, and a psycho diagnostic tool for assessment of psychopathy among forensic and clinical patients and measurement of deviant, irresponsible and impulsive behavior among new entrant into the Nigerian police force during selection processes. Keywords: Hare Psychopathy, Checklist, Forensic Setting, Criminal, Nigeria.